ISLAMIC ART AND ARCHITECTURE: THE INTERSECTION OF THEOLOGY, CULTURE, AND AESTHETICS IN THE MUSLIM WORLD - Rashid Rahman; Nina Anis; Muchlis Daroini (Yayasan Adra Karima Hubbi, 2026)
Islamic art and architecture represent a profound manifestation of the spiritual, cultural, and intellectual traditions of the Muslim world. Throughout history, artistic and architectural expressions in Islamic civilization have not only served aesthetic purposes but have also embodied theological principles and cultural identities. This study aims to analyze how theological concepts, cultural contexts, and aesthetic philosophies interact in shaping Islamic art and architecture across the Muslim world. The study employs a qualitative research design using an interdisciplinary analytical approach that integrates perspectives from Islamic studies, art history, cultural studies, and architectural theory. Data were collected through document analysis of architectural records, historical sources, and scholarly literature, followed by thematic interpretation and comparative analysis of selected Islamic architectural examples. The findings reveal that Islamic art and architecture consistently reflect theological concepts such as tawhid, harmony, and transcendence through geometric ornamentation, calligraphic decoration, and balanced spatial structures. Cultural diversity across regions contributes to stylistic variation while maintaining shared symbolic principles rooted in Islamic belief. The study concludes that Islamic art and architecture function as integrated expressions of theology, culture, and aesthetics, illustrating how religious worldview and cultural identity shape artistic creativity within the Muslim world.